The message and the kingdom : how Jesus and Paul ignited a revolution and transformed the ancient world - Horsley, Richard A.; Silberman, Neil Asher, 1950- (New York : Grossett/Putnam, 1997)
Two distinguished scholars blend archaeology and social history in a new version of the genesis of Christianity. Richard A. Horsley and Neil Asher Silberman reveal how the message of Jesus and Paul was profoundly shaped by the history of their time and by the circumstances and social conditions of the congregations to whom they preached. The authors draw on a wealth of newly uncovered historical information and archaeological discoveries: among others, the soggy timbers of a fisherman's boat submerged in the mud of the Sea of Galilee for more than two thousand years, which suggest the kind of vessel that might have been used by the fishermen-disciples; the ruins of the ancient harbor city of Caesarea, where the name of the notorious Roman governor Pontius Pilate has been identified on a fragmentary Latin inscription; and an ornate urn found in an ancient tomb just south of the Old City of Jerusalem, inscribed with the name of Joseph Caiaphas, the high priest who presided over Jesus' trial. What emerges is a fascinating portrait of Jesus and Paul as great men of faith and passion who were moved by the suffering caused by the dominion of Rome and who offered a renewed religion - a kingdom in which no earthly power would reign.
Map 1: The Province of Judea and surrounding regions in the time of Jesus -- Map 2: The Eastern Mediterranean in the time of Paul -- Prologue: searching for Jesus -- Heavenly visions -- Remaking the Galilee -- Faith healer -- Power and public order -- Preaching the word -- Reviving the nations -- Assemblies of the saints -- Spirits in conflict -- Storming the kingdom -- The Triumph of Caesar -- Keeping the faith -- Timeline 1: The life and times of Jesus of Nazareth -- Timeline 2: The career of Paul.
Includes bibliographical references (p. [261]-277) and index.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Christian antiquities; Rome -- Antiquities